INCOMPLETE CERVICAL DILATATION WITH UTERINE ADHESION AND ITS SURGICAL MANAGEMENT IN A NON-DESCRIPT DOE - T. Sarath; S. Pravina; R. Rajkumar; A. Thangamani; A. Reshma; S. Manokaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A case of dystocia due to incomplete cervical dilation consequent to uterine adhesion in non-descript doe and its surgical management was reported in this paper.